2006
DOI: 10.1017/s0967199406003546
|View full text |Cite
|
Sign up to set email alerts
|

Nitric-oxide-dependent activation of pig oocytes: the role of the cGMP-signalling pathway

Abstract: Pig oocytes matured in vitro were parthenogenetically activated (78%) after treatment with 2 mM nitric oxide-donor (+/-)-S-nitroso-N-acetylpenicillamine (SNAP) for 24 h. Inhibition of soluble guanylyl cyclase with the specific inhibitors 1H-[1,2,4]oxadiazolo[4,3-a]quinoxalin-1-one (ODQ) or 6-anilino-5,8-quinolinequinone (LY83583) suppressed the SNAP-induced activation in a dose-dependent manner (23% of activated oocytes after treatment with 400 microM ODQ; 12% of activated oocytes after treatment with 40 micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…In fact, the effect of NO on oocyte maturation can be stimulatory or inhibitory depending on its concentration (Bu et al, 2003(Bu et al, , 2004Bilodeau-Goeseels, 2007). Positive effects of SNAP administration during IVM were observed in the mouse (Goud et al, 2005), rat , and pig (Petr et al, 2005(Petr et al, , 2006. In our IVM system, the addition of 100 µM SNAP slightly increased blastocyst and hatching rates of oocytes derived from Lo ovaries to a percentage comparable with that observed in oocytes isolated from Hi ovaries; conversely, it negatively affected the hatching rate of oocytes from Hi ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the effect of NO on oocyte maturation can be stimulatory or inhibitory depending on its concentration (Bu et al, 2003(Bu et al, , 2004Bilodeau-Goeseels, 2007). Positive effects of SNAP administration during IVM were observed in the mouse (Goud et al, 2005), rat , and pig (Petr et al, 2005(Petr et al, , 2006. In our IVM system, the addition of 100 µM SNAP slightly increased blastocyst and hatching rates of oocytes derived from Lo ovaries to a percentage comparable with that observed in oocytes isolated from Hi ovaries; conversely, it negatively affected the hatching rate of oocytes from Hi ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…sGC and cGMP also play an important role in the ovary (Grasselli et al, 2001;LaPolt et al, 2003;Shi et al, 2004) and it was proved that they are also involved in the regulation of meiosis (Tornell et al, 1984(Tornell et al, , 1990. Petr et al (2006) demonstrated that the activation of in vitro matured pig oocytes via the NO-dependent signalling pathway was mediated through cGMP. This suggestion is supported by an observation that sGC inhibitors effectively suppressed oocyte activation after the treatment of oocyte with an NO-donor and this is further supported by an observation that 8-Br-cGMP -an analogue of cGMP more resistant to phosphodiesteraseenhances the effects of a suboptimal dose of the NO-donor SNAP on oocyte activation.…”
Section: Which Processes Are Specific To No-induced Oocyte Activation?mentioning
confidence: 99%
“…Changes in intracellular signalling by free calcium ions seem to be important for oocyte activation using NO-donor, and these changes are at least partially triggered by the cGMP-dependent signalling cascade (Kuo et al, 2000;Petr et al, 2005bPetr et al, , 2006Petr et al, , 2007a. These effects on calcium signalling could mimic the intracellular oscillation of free calcium ions which is induced by phospholipase C-zeta after fertilization of the oocyte by sperm (Jones et al, 1998;Parrington et al, 2002;Fujimoto et al, 2004;Konig et al, 2006).…”
Section: Discussionmentioning
confidence: 99%